Pelatihan Pembuatan Infografis dan Reklame dengan Menggunakan Canva Sebagai Sarana Adaptasi Teknologi Pembelajaran - Yayak Kartika Sari; Agung Prasetya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
In this modern era, technological advancements have reached their peak, impacting almost every aspect of human life. In education at schools, educators must also be able to provide innovation to their students so that they are more motivated to learn. To do this, educators can use digital technology to create different and still educational learning content, but there are several obstacles faced at SDN 1 Rejosari, namely the lack of a computer lab, resulting in insufficient implementation of technology in the curriculum. Thus, the goal of this community service is to introduce infographics and advertisements using the Canva application, aimed at enhancing the creativity of the students at SDN 1 Rejosari. This community service activity began with the preparation stage, the implementation stage, and the evaluation stage. The results of the evaluation stage showed a percentage of 90 – 100% in understanding the introduction to the material presented, but in practice, only 65% was achieved. Therefore, further action is needed, specifically continuous training on infographic and advertisement design using Canva.